2017
DOI: 10.1093/femsle/fnx145
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model of azithromycin-induced persistent Chlamydia trachomatis infection

Abstract: Single-dose azithromycin is recommended for treating Chlamydia trachomatis infections. Here, we established an in vitro cell model of azithromycin-induced persistent infection. Azithromycin inhibited the replication of C. trachomatis in a dose-time-dependent manner. Electron microscopy indicated that small inclusions in the induced model contained enlarged, aberrant and non-infectious reticulate bodies. RT-PCR showed that C. trachomatis still has the ability to express the unprocessed 16S rRNA gene in the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Moreover, heterotypic resistance in various Chlamydia species has been observed upon survival of a small proportion of bacteria exposed to antibiotic concentrations well above the minimal inhibitory concentration (MIC) and might be a cause of treatment failure in patients, a phenomenon also referred to as drug indifference, tolerance, or persistence ( Suchland et al, 2003 ; Sandoz and Rockey, 2010 ). In Chlamydia , persistence, or the chlamydial stress response, is known to occur specifically upon exposure to antibiotics affecting cell wall synthesis, such as penicillin ( Lewis, 2007 ; Sandoz and Rockey, 2010 ; Schoborg, 2011 ; Borel et al, 2014 ; Zheng et al, 2015 ; Leonard et al, 2017 ; Xue et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heterotypic resistance in various Chlamydia species has been observed upon survival of a small proportion of bacteria exposed to antibiotic concentrations well above the minimal inhibitory concentration (MIC) and might be a cause of treatment failure in patients, a phenomenon also referred to as drug indifference, tolerance, or persistence ( Suchland et al, 2003 ; Sandoz and Rockey, 2010 ). In Chlamydia , persistence, or the chlamydial stress response, is known to occur specifically upon exposure to antibiotics affecting cell wall synthesis, such as penicillin ( Lewis, 2007 ; Sandoz and Rockey, 2010 ; Schoborg, 2011 ; Borel et al, 2014 ; Zheng et al, 2015 ; Leonard et al, 2017 ; Xue et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated that the RSK inhibitors LJH685 and LJI308 reduced Chlamydia infection in three cell lines, while siRNA-mediated RSK knockdown inhibited Chlamydia negative for mycoplasma infection as determined by a detection kit according to the manufacturer's recommendations (Bioind, Tel Aviv, Israel). Chlamydia was propagated as previously described (Xue et al, 2017).…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
“…Besides euo, the late gene omcB, encoding the outer membrane complex protein B, is also considered as a molecular marker of persistence. omcB is down-regulated in persistent Chlamydia induced either by iron deprivation, interferon-γ or azithromycin [33,63,[72][73][74]. In contrast, OmcB protein levels were unaffected in iron-starved C. pneumoniae [75].…”
Section: Discussionmentioning
confidence: 99%